Marginalisasi Daun-Daunan Hijau dalam Pola Konsumsi Pangan di Jawa pada Abad Ke-19 dan Ke-20 - Yuanita Wahyu Pratiwi (Lembaran Sejarah, 2023)
Despite being home to one of the world’s richest biodiversity, dietary preferences in Java have shifted away from the type of vegetable typically abundant tropical region: leafy greens. This article explains the changing palate of Java’s inhabitants using environmental, economic, and cultural lenses. The method used consisted of analysing determining factors in the development of diet in the 19th and 20th centuries such as the development of public health science, government policies, economic condition, the development of food industry, and the development of media. This research discovers that leafy greens gradually become marginalized over these two centuries due to 1) food security management that was increasingly dependent on utilization of modern nutritional science, modern agriculture, and centralized distribution chain, and 2) centralized dietary guidance by the government and media. This article also suggests that by moving beyond studying food as a mere cultural expression to also studying food as a foodstuff that incorporate its provisioning and availability factors, we can unravel not only the changes in interhuman relations but also in human-nature relations.